Effects of Dehydroeffusol on Spasmogen-Induced Contractile Responses of Rat Intestinal Smooth Muscles - Di, Fan; Zhai, Haifeng; Li, Peng; Huang, Jianmei (Planta Medica, 2014)
Dehydroeffusol is a naturally occurring phenanthrene isolated from Juncus effusus. In the context of screening new drugs against gastrointestinal spasms, we investigated its effects on isolated rat jejunum in vitro. Dehydroeffusol (30–90 µM) slightly and transiently enhanced contractions in a concentration-dependent manner but significantly inhibited the contractions induced by KCl (100 mM), (±)-Bay-K8644 (5 µM), pilocarpine (90 µM), and histamine (100 µM). These results show that dehydroeffusol may antagonize the spasmogenic activity of various agents, and therefore, could be a promising agent in the treatment of spasms. Its potential spasmolytic mechanism is also discussed.
Keywords: dehydroeffusol; rat jejunum; spasmolytic; smooth muscle; Juncus effusus; Juncuaceae